PRODUK HALAL DALAM PERSPEKTIF HUKUM DAN MASYARAKAT - Safik Faozi; Adi Suliantoro; Fitika Andraini; Arikha Saputra (Jurnal Ilmiah Dinamika Hukum, 2023)
Nowadays, food and beverage products are widely circulated in society. In the era of globalization of society, the traffic of goods including food/drinks across countries is not guaranteed to be halal. Even though religious obligations command us to consume halal food/drinks. With the existence of Law no. 33 of 2014 concerning Halal Product Guarantees and Government Regulation no. 39 of 2021 shows that there is legal certainty in the implementation of Halal Product guarantees. The problem is how to theoretically and empirically study the implementation of halal product guarantees from an Indonesian legal perspective. The research methods are normative juridical and sociological. The research results show that theoretically, the implementation of halal product guarantees is based on Law no. 33 of 2014 concerning Halal Product Guarantees reflects legal norms originating from God's Law (God Order), namely from the Al-Qur'an and Hadith, and has long been practiced in people's lives as a reflection of a person's or society's religious awareness. The process shows a circle of interaction that ends with the Halal Product Guarantee Law. Empirical studies explain that the implementation of halal product guarantees has been going on in people's lives for a long time so that it functions to create legal certainty, comfort and justice for the user community as well as realizing beneficial values for economic growth and community welfare. The existence of statutory regulations, legal institutions and public awareness of halal product guarantees are elements of a legal system. Empirical studies explain that the economic subsystem played by business actors has great energy to adapt quickly and utilize legal regulations and community culture to expand and develop their business. Keywords: Halal, Products, Law and Society